Barn owls evolution and ecology - Roulin, Alexandre 1968- (Cambridge University Press, 2020)
With heart-shaped face, buff back and wings, and pure white underparts, the barn owl is a distinctive and much-loved bird which has fascinated people from many cultures throughout history. How did the barn owl colonise the world? What adaptations have made this bird so successful? How is the increasing impact of human disturbance affecting these animals? Answering these questions and more, Roulin brings together the main global perspectives on the evolution, ecology and behaviour of the barn owl and its relatives, discussing topics such as the high reproductive potential, physiology, social and family interaction, pronounced colour variation and global distribution. Accessible and beautifully illustrated, this definitive volume on the barn owl is for researchers, professionals and graduate students in ornithology, animal behaviour, ecology, conservation biology and evolutionary biology, and will also appeal to amateur ornithologists and nature lovers.